ANTIOXIDANT ACTIVITY AND ANTIBACTERIAL SCREENING OF TUBERS OF AMORPHOPHALLUS KONKANENSIS AND AMORPHOPHALLUS BULBIFER (ARACEAE) - Shete, Chidanand C.; Wadkar, Suryakant S.; Gaikwad, Nikhil B.; Patil, Kumar S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: Antioxidant activity (AOA) and antibacterial screening of tubers of unexplored Amorphophallus konkanensis Hett., Yadav & Patil (AKT) and Amorphophallus bulbifer (Roxb.) Bl. (ABT). Methods: Antioxidant activity was evaluated by using ferric reducing antioxidant power (FRAP), 1 1-diphenyl-2-picrylhydrazyl (DPPH) radical, hydroxyl (OH•) radical, nitric oxide (NO∙) radical scavenging activities. Phenolics were determined by total phenolic content (TPC) assay. Antibacterial screening of different solvent extracts of tubers was tested against Gram positive and Gram negative bacterial strains by using the agar diffusion method. HPLC analysis was carried out for active phenolic compounds. Results: Tubers were extracted with three different solvents (ethanol, acetone and water). Acetone extracts of AKT and ABT exhibited the highest phenolic content 29.37±0.83 and 20.62±1.04 mg GAE/g. The AKT and ABT acetone extracts possesses highest free radical scavenging activity towards FRAP (0.632 & 0.586 O. D), DPPH (85.78% & 82.68%), hydroxyl (OH∙) radical (82.43% & 80.26%), nitric oxide (NO∙) radical (81.34% & 80.8%). The phenolic compounds tannic acid, gallic acid, quercetin, p-coumaric acid, catechin were identified by the HPLC method in acetone extracts. Among the different extracts, acetone extract of both the species of Amorphophallus showed significant antibacterial activity against all Gram positive and Gram negative bacterial strains tested. Conclusion: The results indicated that AKT and ABT can be considered as good sources of natural antioxidant for medicinal, commercial, nutraceutical and functional food applications. Antibacterial efficacy shown by these plants provides a scientific basis for their traditional uses in remedies.